PHYSICAL ACTIVITY AMONG OLDER ADULTS AT RISK FOR FALLS: BASELINE FINDINGS FROM STURDY. (16th November 2018) - Schrack, J; Urbanek, J; Wanigatunga, A; Juraschek, S; Michos, E; Roth, D; Appel, L
Abstract: Despite strong evidence that physical activity (PA) is linked to health and the risk of falling in older adults, little is known about the association between free-living PA and falls in this population. Using baseline data from the Study To UndeRstand vitamin D and falls reduction in You (STURDY), an ongoing clinical trial of vitamin D supplementation and falls, we assessed the relationship between prior fall history and objectively measured PA collected over 7-days in the free-living environment among 532 older adults (56% male, mean age 76, range 70–97). Linear regression models predicting PA from falls history after adjusting for age, BMI, serum 25-hydroxyvitamin D, sex, race, and self-described fear of falling. Compared to those with no reported falls in the past year, older adults who reported one fall (n=142, 27%) were more active (p=0.04), while those who reported two or more falls (n=184, 35%) tended to be less active (p=0.07). Additionally, more active participants were more likely to be younger, male, white, and have a lower BMI (p<0.05 for all). These results suggest a complex association between daily PA and falls that may differ among older adults with a fear falling or the occurrence of multiple falls. Further analyses of activity patterns and longitudinal trends is warranted to further our understanding of this complex relationship, and help define the most relevant falls prevention interventions for relatively active versus sedentary older adults.